2019
DOI: 10.3177/jnsv.65.66
|View full text |Cite
|
Sign up to set email alerts
|

Auraptene/Naringin-Rich Fruit Juice of <i>Citrus kawachiensis</i> (Kawachi Bankan) Prevents Ischemia-Induced Neuronal Cell Death in Mouse Brain through Anti-Inflammatory Responses

Abstract: Cerebral ischemia/reperfusion leads to delayed neuronal cell death, resulting in brain damage. Auraptene (AUR) and naringin (NGIN), which exert neuroprotective effects in ischemic brain, are abundant in the peel of Citrus kawachiensis. Although parts of AUR/NGIN are transited from the peel to the juice during the squeezing of this fruit, these amounts in juice might be too low to exert effects. We thus prepared the AUR/NGIN-rich fruit juice of C. kawachiensis by addition of peel paste to the raw juice. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In addition, we recently reported that the peel of C. kawachiensis, a rich source of AUR, is neuroprotective in LPS-induced systemic inflammatory model mice [4], senescence-accelerated mice [29], global cerebral ischemia model mice [30], type-2 diabetic db/db mice [31], and an LPS-induced mouse model of PD [32]. We also showed that the AUR-rich fruit juice of C. kawachiensis, made by the addition of peel paste to the raw juice, significantly suppressed the ischemia-induced neuronal cell death in the hippocampus of ischemic mice [33] and that this juice contributed to the preservation of cognitive function of healthy volunteers [34]. In these reports, we confirmed that the basis of this neuroprotective ability might have been anti-inflammatory effect of AUR.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, we recently reported that the peel of C. kawachiensis, a rich source of AUR, is neuroprotective in LPS-induced systemic inflammatory model mice [4], senescence-accelerated mice [29], global cerebral ischemia model mice [30], type-2 diabetic db/db mice [31], and an LPS-induced mouse model of PD [32]. We also showed that the AUR-rich fruit juice of C. kawachiensis, made by the addition of peel paste to the raw juice, significantly suppressed the ischemia-induced neuronal cell death in the hippocampus of ischemic mice [33] and that this juice contributed to the preservation of cognitive function of healthy volunteers [34]. In these reports, we confirmed that the basis of this neuroprotective ability might have been anti-inflammatory effect of AUR.…”
Section: Discussionmentioning
confidence: 76%
“…In the future, we would like to investigate the effect of AUR on microglial cells, for example, using N9 cells. The peel of Citrus grandis (Kawachi bankan), a rich source of AUR [21], might become a natural medicine in the future, as suggested previously [22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 95%
“…Naringin has a strong ONOO − scavenging ability and can inhibit ONOO − -mediated mitosis, NADPH oxidase, iNOS, NO production, and protect against ischemia-reperfusion injury [63]. In addition, naringin can reduce neuronal death and inhibit the over activation of astrocytes and microglia after ischemic injury in tMCAO mice [64,65]. In the OGD model of neuronal cells, naringin pretreatment can activate the PI3K/AKT pathway, improve cell viability, and inhibit the secretion of inflammatory factors such as TNF-α and IL-6 [66].…”
Section: Flavonoidsmentioning
confidence: 99%